Adhesive joint geometry variation in non-rigid aircraft structures - Coladas Mato, Pablo (Cranfield University, 2019)
Adhesive bonding is a proven alternative to mechanical fasteners for structural assembly, offering lighter and thus more fuel efficient aircraft and cost-effective manufacturing processes. The effective application of bonded structural assemblies is however limited by the tight fit-up requirement, which is with tolerance ranges of hundreds of microns; this can be a challenge for the industry to meet considering the variability of current part manufacturing methods and the conservative nature of the conventional tolerance stack-up analysis method. Such a (perceived) limitation can discourage effective exploitation of bonding technologies, or lead to development of overengineered solutions for assurance. This work addresses such challenge by presenting an enhanced bondline thickness variation analysis accounting for part deflection of a bonded skinstringer assembly representing a typical non-rigid airframe structure. A semianalytical model accounting for unilateral contact and simplified 1D adhesive flow has been developed to predict bondline thickness variation of the assembly given the adherends’ mechanical properties, adhesive rheological properties, and external assembly forces or boundary conditions. A spectral-analysis method for assembly force requirement estimation has also been tested. The bondline dimensions of several representative test articles have been interrogated, including a reconfigurable test assembly designed specifically to test the input conditions that affect bondline geometry variation. It has been demonstrated that the part deflections need to be accounted for regarding the fit-up requirement of bonded non-rigid structural assembly. The semi-analytical model has been found to more reliable and realistic prediction of bondline thickness when compared to a rigid tolerance stack-up. The analysis method presented can be a major technology enabler for faster, more economical development of the aircraft of the future, as well as of any analogue structures with high aspect ratios where weight savings and fatigue performance may be core objectives.
Keywords: Adhesive; Aerospace; Assembly; Deflection; Deformable assemblies; Direct Linearization Method; Finite Element Analysis; Flexible assemblies; Metal-tometal bonding; Non-rigid assemblies; Quadratic Programming; Skin; Squeezeflow; Stringer; Unilateral contact; Viscous flow